Energy Performance and Economic Feasibility Comparison of Evacuated Tube and Flat Plate Solar Collectors for Domestic Water Heating - Ezzeddine, Mohamad Riyad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The study provides performance analysis and economic feasibility examination of Solar Domestic Water Heating (SDWH) Systems employing two different types of solar collectors, Flat Plate Collector (FPC) and Evacuated Tube Collector (ETC). The work studies the system performance, solar system fraction, collector and storage tank outlet temperatures, collected energy, and the system efficiency. The performance analysis of the two solar water heating systems was carried out considering the annual weather conditions of Beirut city by using T*SOL® and TRNSYS Simulation tools. Results showed that the annual efficiency of SDWH using ETC (44%) was 4 points more than the annual efficiency of SDWH employing FPC (40%). The annual solar fraction of SDWH with ETC (89%) is found to be 9 points more than that of FPC (80%). This makes the system with ETC more effective in terms of energy performance, leading to more economic benefits over its life of the operation. This has been proved by evaluating both systems' economic feasibilities over their operation life (20 years). The economic feasibility results showed that the total savings of SDWH using ETC is $ 47,615, and the saving-to-investment ratio is 7.7. The total savings of the system using FPC is $ 42,840, and saving-to-investment ratio is 7. Keywords: Solar domestic water heating, solar collectors, Flat plat collector, Evacuated tube collector, Performance analysis, Economic feasibility.

ÖZ:Bu çalışma kullanım suyu ısıtılmasında yararlanılan iki farklı güneş toplayıcı düzeneğini karşılaştırmalı olarak incelemeyi amaçlamaktadır. Çalışma düz plakalı ve vakum tüplü güneş toplayıcı düzeneklerinin performansını ve ekonomik fizibilitesini ortaya koymaktadır. Dikkate alınan göstergeler toplanan enerji, güneş enerjisi katkı oranı, düzenek performansı ve verimi ile toplayıcı ve depo çıkış sıcaklıklarıdır. Düzeneklerin performans karşılaştırması Beyrut hava koşulları dikkate alınarak TRNSYS ve T*SOL yazılımları ile oluşturulan modellerin simülasyon sonuçlarının tetkiki ile gerçekleştirilmiştir. Sonuçlar vakum tüplü toplayıcının yıllık veriminin (% 44) düz plakalı toplayıcının yıllık veriminden (% 40) 4 puan daha yüksek olduğunu göstermektedir. Bunun yanında vakum tüplü toplayıcının yıllık güneş enerjisi katkı oranının (% 89) düz plakalı toplayıcının güneş enerjisi katkı oranından (% 80) 9 puan daha fazla olduğu ortaya çıkarılmıştır. Bu durum vakum tüplü güneş toplayıcı düzeneğin enerji performansının daha iyi olduğunu göstermekte ve çalışma süreci boyunca daha fazla ekonomik fayda sağlayacağı sonucunu doğurmaktadır. Yapılan ekonomik fizibilite çalışmasının sonucu da bunu göstermektedir. Yapılan çalışmada vakum tüplü güneş toplayıcısının kullanım suyu ısıtılmasında faydalanılması ile yirmi yıllık çalışma süresi boyunca Beyrut koşullarında toplam 47,615 $ tasarruf edileceği ve tasarruf-yatırım oranının ise 7.7 olacağı hesaplanmıştır. Düz plakalı güneş toplayıcısının kullanılması durumunda ise toplam tasarrufların 42,840 $, tasarruf yatırım oranının ise 7 olacağı bulunmuştur. Anahtar Kelimeler: Güneş enerjisi ile kullanım suyu ısıtılması, Güneş toplayıcıları, Vakum tüplü güneş toplayıcısı, Düz plakalı güneş toplayıcısı, Performans analizi, Ekonomik fizibilite.
Master of Science in Mechanical Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2021. Supervisor: Assoc. Prof. Dr. Murat Özdenefe.
Keywords: Solar energy-Heat; Heat and Power; Solar domestic water heating; solar collectors; Flat plat collector; Evacuated tube collector; Performance analysis; Economic feasibility